Quizlet interactive learning: Junior high school students' perspective to enrich English vocabulary - Nisa Febriyanti Tanjung; Tien Rafida (Curricula: Journal of Curriculum Development, 2025)
Changes due to technology are also very much felt in the world of education, where technology has brought about changes in the teaching and learning process. This study examines the perspectives of junior high school students on using Quizlet as an interactive learning tool to enhance their English vocabulary. Employing a mixed-methods approach with a convergent parallel design, the research involved 30 eighth-grade students from a junior high school in Medan. Data were collected through questionnaires, interviews, and classroom observations, then analyzed using thematic analysis. The results revealed five dominant themes from students' perceptions: Quizlet is user-friendly, interactive through games and flashcards, effective in improving vocabulary retention through repetition, motivating due to its engaging features, and flexible for independent learning at any time and from anywhere. These findings demonstrate that Quizlet not only supports vocabulary mastery but also fosters student engagement and motivation, aligning with principles of Mobile-Assisted Language Learning (MALL). The study suggests that integrating digital applications, such as Quizlet, can enhance the quality of English language teaching, particularly in vocabulary development. Educators are encouraged to adopt such tools to create more interactive and student-centered learning environments. Future research should investigate the long-term effects of using Quizlet and assess its effectiveness across different educational contexts and learner levels.   Abstrak Perubahan akibat teknologi juga sangat terasa di dunia pendidikan, di mana teknologi telah membawa perubahan dalam proses belajar mengajar. Penelitian ini mengeksplorasi perspektif peserta didik sekolah menengah pertama terhadap penggunaan Quizlet sebagai media pembelajaran interaktif untuk memperkaya kosakata bahasa Inggris. Menggunakan mixed methods dengan desain paralel konvergen, penelitian ini melibatkan 30 peserta didik kelas VIII dari salah satu SMP di Medan. Data dikumpulkan melalui angket, wawancara, dan observasi kelas, lalu dianalisis dengan analisis tematik. Hasil penelitian mengungkapkan lima tema utama dari persepsi peserta didik: Quizlet mudah digunakan, interaktif melalui permainan dan flashcard, efektif dalam meningkatkan daya ingat kosakata melalui pengulangan, memotivasi karena fitur-fiturnya yang menarik, serta fleksibel karena memungkinkan pembelajaran mandiri kapan saja dan di mana saja. Temuan ini menunjukkan bahwa Quizlet tidak hanya mendukung penguasaan kosakata, tetapi juga meningkatkan keterlibatan dan motivasi belajar peserta didik, sejalan dengan prinsip Mobile-Assisted Language Learning (MALL). Implikasi dari studi ini adalah bahwa integrasi aplikasi digital seperti Quizlet dapat meningkatkan kualitas pengajaran bahasa Inggris, khususnya dalam pengembangan kosakata. Pendidik disarankan untuk memanfaatkan media digital ini guna menciptakan pembelajaran yang lebih interaktif dan berpusat pada peserta didik. Penelitian selanjutnya disarankan untuk mengkaji dampak jangka panjang penggunaan Quizlet serta efektivitasnya di berbagai konteks dan jenjang pendidikan. Kata Kunci: kosakata; pembelajaran interaktif; Quizlet